Media Activism: Bantay Kalikasan in the Passage of the Clean Air Act - Frago, Perlita M. (Philippine Political Science Journal; Vol 29 No 52 (2008), 2009)
This case study examines the role of media in the enactment of the Clean Air Act (CAA) of 1999. Through the intervention of the Bantay Kalikasan (Nature Watch), the environmental advocacy arm of the ABS-CBN, the largest broadcasting network of the Philippines, the clean air discourse became a public issue. It not only campaigned actively for the law by initiating roadside information teams, but it also initiated the 5M–signature campaign in support of the CAA’s enactment into law. Most of all, it amplified the discursive health and moral debates popularized by the Clean Air coalition concerning incinerators. Environment is not exactly a mainstream issue in the Philippines, but the media possess the essential resources to make any dire environmental issue a public concern. As soon as the media realize their discursive power to popularize any technical environmental concern, the more realizable the future will be for a more viable and more continuous environmental policy not only for clean air.